Label-free quantitative proteomics reveals the mechanism of microwave-induced Tartary buckwheat germination and flavonoids enrichment. (October 2022) - Wang, Simeng; Wang, Shunmin; Wang, Junzhen; Peng, Wenping
Graphical abstract: Highlights: Microwave treatment altered the protein expression of germinated Tartary buckwheat. Differentially expressed proteins involved in germination and flavonoids enrichment were mapped to KEGG pathways. Differentially expressed proteins were related to energy production and conversion and gene expression. Upregulated proteins promoted flavonoids accumulation after microwave treatment. Abstract: The objective of this study was to reveal the mechanism underlying the effects of microwave treatment on Tartary buckwheat germination and flavonoids enrichment. Label-free quantitative proteomic analysis showed that Tartary buckwheat germinated at 3, 5, and 7 days after 300 W/50 s microwave treatment had 7, 5, and 5 differentially expressed proteins (DEPs) compared to those of control. These DEPs are mainly related to energy production and conversion, gene expression, and flavonoids metabolism. Based on KEGG analysis, the DEPs were mainly enriched in photosynthesis, RNA polymerase, flavonoid biosynthesis, phenylalanine metabolism, and phenylpropanoid biosynthesis metabolic pathways. Further, the upregulation of phenylalanine ammonia-lyase and flavonol synthase protein enzymes promoted germination and flavonoids accumulation in Tartary buckwheat. These findings reveal the mechanism of Tartary buckwheat germination and the enrichment of flavonoids induced by microwaves and provide a scientific basis for the development of functional foods for Tartary buckwheat.